1999
DOI: 10.1016/s0896-6273(00)81033-8
|View full text |Cite
|
Sign up to set email alerts
|

Bone Morphogenetic Proteins Are Required In Vivo for the Generation of Sympathetic Neurons

Abstract: Bone morphogenetic proteins (BMPs) induce autonomic neurogenesis in neural crest cultures and stimulate sympathetic neuron development when overexpressed in vivo. We demonstrate that inhibition of BMPs in the chick embryo bythe BMP antagonist Noggin prevents sympathetic neuron generation. In Noggin-treated embryos, the noradrenergic marker genes tyrosine hydroxylase (TH) and dopamine-beta-hydroxylase (DBH), panneuronal neurofilament 160 (NF160) and SCG10 genes, and the transcriptional regulators Phox2b and Pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
174
0
3

Year Published

2000
2000
2019
2019

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 274 publications
(182 citation statements)
references
References 52 publications
(3 reference statements)
4
174
0
3
Order By: Relevance
“…Sympathoadrenal neural crest cells including those on their way to the adrenal anlage normally start to express Mash1 and Phox2b (Lo et al, 1998;Pattyn et al, 1999) under the influence of BMPs from the dorsal aorta (Reissmann et al, 1996;Schneider et al, 1999). The fact that sympathoadrenal neural crest cells at those axial levels where the adrenal medulla forms mostly fail to express Phox2b in Sox10-deficient embryos is compatible with the postulated role of Sox10 in Phox2b induction.…”
Section: Discussionmentioning
confidence: 85%
“…Sympathoadrenal neural crest cells including those on their way to the adrenal anlage normally start to express Mash1 and Phox2b (Lo et al, 1998;Pattyn et al, 1999) under the influence of BMPs from the dorsal aorta (Reissmann et al, 1996;Schneider et al, 1999). The fact that sympathoadrenal neural crest cells at those axial levels where the adrenal medulla forms mostly fail to express Phox2b in Sox10-deficient embryos is compatible with the postulated role of Sox10 in Phox2b induction.…”
Section: Discussionmentioning
confidence: 85%
“…Such factors include BMP2͞4, which drives NCC to autonomic sympathetic-like neuronal fate (18)(19)(20); neuregulin-1 and Notch ligands, which favor gliogenesis (21)(22)(23); and endothelin 3 (ET3), which promotes survival and proliferation of glial-melanocytic (GM) bipotent precursors as well as committed melanocytic and glial cells (24)(25)(26).…”
mentioning
confidence: 99%
“…This seems to be the first report of neuronal migration in the peripheral nervous system. The most extensively studied neural crest-derived peripheral neurons are sympathetic and sensory neurons, most of which do not differentiate into neurons until after their precursors have reached their final destination (Schneider et al, 1999). However, examination of fixed embryos has shown that the superior cervical ganglion forms from cells that first migrate ventrally to form a column of cells that is continuous with the stellate ganglion primordium at lower cervical levels; some cells subsequently migrate rostrally to form the superior cervical ganglion (Rubin, 1985).…”
Section: Differentiation and Cell Migrationmentioning
confidence: 99%
“…Although neuronal migration is common in the developing CNS, there is currently little evidence about whether developing peripheral neurons can migrate. In developing parasympathetic, sympathetic and dorsal root ganglia, the neural crest-derived precursors arrive at their final destination before differentiating into neurons (Schneider et al, 1999;Muller and Rohrer, 2002).…”
Section: Introductionmentioning
confidence: 99%